Kultura drogą nadziei. Z nauczania kard. Stefana Wyszyńskiego, prymasa Polski - Dziuba, Andrzej (Społeczeństwo, 2022)
Man realizes their humanity on the paths of the earthly pilgrimage. Above all, it constitutes an abundance of references to truth, goodness, beauty and sacrum. Culture is the totality of products of mankind that have been personally accepted and found their place in the ethical and moral as well as psychological and spiritual life. Questions regarding culture are, at the same time, questions about the value system, which approve and develop the man and the entire human family. The issue of culture was the point of particular interest for Cardinal Stefan Wyszyński. It resulted, among others, from the specific nature of the contemporary circumstances of evangelization, as well as of the social and political situation. The Polish Primate thought that field to be an important plain for the mission of the Church. Among others, it included remembrance with the concurrent involvement in the present and the future. In practice, one may easily notice that culture depends, to a greater extent than it has been usually considered, on collective and individual ethical and moral stands and choices.